Role of pre-operative shower with common soap to prevent postoperative wound infection in routine and emergency Laparotomy - Mazumder, Anup Kumar; Faruquzzaman; Ali, Md. Showkat (The Insight, 2022)
Background: In different research studies and metaanalysis, it has been already established that preoperative shower with Chlorhexidine has protective role to prevent and reduce surgical site infections. However, in many guidelines, including the National Institute of Health and Care Excellence (NICE) guideline, UK, the role of showering is not recommended. Aims & objectives: The aim of this research is to depict the role of preoperative showering to reduce surgical site infections. Methodology: This was a prospective study with a total 308 patients of Laparotomy in Khulna Medical College Hospital, Bangladesh, from January 2016 to December 2020. Convenient purposive sampling was the sampling method. Ethical clearance was taken individually from patient and from the ethical review committee of Khulna Medical College Hospital. Results: Among the total 308 patients, 240 and 62 patients had emergency and routine Laparotomy respectively. 18.8% patients with emergency laparotomy (Group A) had surgical site infections, whereas 6.4% patients with routine laparotomy had surgical site infections. According to the Southampton wound grading system, in Group A, surgical site infections were either deep or organ space infections (Grade IV or V), whereas, in Group B, all infections were superficial (Grade II). In case of routine surgery, where the patients had a shower preoperatively at the day or before the day of operation, wound infection was nil.When the patients had no shower within 05 days prior to emergency surgery, the infection rate was 8.8%.And when the patients had a shower within 2-5 days prior to surgery, the infection rate was 7.1%. The patients who had a shower 01 day before surgery or at the day of surgery, the infection rateswere 2.1% and nil respectively. Conclusion: Taking shower with common soap before surgery reduces the rate of surgical site infections. Shower prior to or at the day of surgery greatly influences the overall infective outcome. Therefore, shower and it timing is an important factor in relation to both routine and emergency surgery.